The Influence of Finger Puppet Learning Media to Students' Speaking Skills and Self-Confidence in English Learning - Mumtaz Hsb, Dara Ophelia; Ekayati, Rini (Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines the effect of finger puppet learning media on students’ speaking skills and self-confidence in English learning. Conducted at Muslim Suksa School in Southern Thailand, the research employed a quantitative quasi-experimental method using a nonequivalent control group design. The sample comprised 30 second-grade high school students selected through purposive sampling. Data were collected through pretest and posttest instruments adapted from previous studies and analyzed using descriptive statistics and hypothesis testing. The findings reveal a significant improvement in students’ speaking skills and self-confidence following the use of finger puppets. The mean score increased from 60.28 to 84.32, while the standard deviation decreased from 15.007 to 9.860. A paired samples t-test yielded a t-value of −10.635 with a significance level of 0.000 (p 0.05), indicating a statistically significant difference between pretest and posttest results. These results suggest that finger puppet media effectively reduce students’ psychological barriers by creating a sense of distance between speakers and their audience, supporting authentic task-based learning, and fostering a more relaxed classroom atmosphere. Moreover, in Muslim school contexts, finger puppets can be culturally adapted to align with students’ religious values, thereby supporting learning while preserving local identity.